A new tapered semiconductor laser with integrated multimode interference coupler - Zhang, Jianxin; Sun, Haizhu; Du, Zaifa; Yang, Min; Wang, Pingping; Zhang, Yingchao; Fan, Xinmin (Frontiers in Physics, 2025)
A new tapered semiconductor laser with an integrated multimode interference coupler is presented in this paper. The seed source of the new laser is a multimode interference coupler semiconductor laser, which overcomes the limitations imposed by the relationship between single mode output and gain medium volume in the ridged waveguide region. The simulation results show that the multi-mode interference coupler can effectively provide a spatial single-mode seed light source for the tapered output waveguide, and the tapered output waveguide of the tapered semiconductor laser can also effectively reduce the optical power density of the output laser, which verifies the feasibility of the design scheme and provides a new idea for the design of high beam quality and high power tapered semiconductor laser.